Evaluasi Kinerja Strategi Sinyal Prioritas Bus pada Sistem Bus Rapid Transit - Yulianto, Budi (Department of Civil Engineering, Diponegoro University, 2025)
Population growth and rapid urbanization have increased transportation demand and triggered traffic problems. Capacity-based approaches often exacerbate these conditions, highlighting the need for a sustainable transportation concept. The government has designated the development of public transportation as a national priority program, one of which is through bus rapid transit (BRT). To ensure the efficiency, reliability, and attractiveness of BRT, the implementation of bus signal priority (BSP) is essential. This study aims to evaluate the performance of passive and active BSP strategies at signalized intersections within a BRT system using VISSIM microscopic simulation. The strategies analyzed include cycle time adjustment, phase splitting, red truncation, green extension, and phase insertion. The simulation results indicate that the most effective strategies are cycle time adjustment with the early cut off concept for passive BSP and phase insertion for active BSP. The performance of BSP strategies is influenced by the number of phases, traffic movement patterns, and bus service frequency, which vary according to the applied strategy. This study recommends selecting BSP strategies through comprehensive simulation study to achieve both effective performance and cost efficiency before implementation.